If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -76 = 39y + -44y Combine like terms: 86 + -76 = 10 10 = 39y + -44y Combine like terms: 39y + -44y = -5y 10 = -5y Solving 10 = -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 10 + 5y = -5y + 5y Combine like terms: -5y + 5y = 0 10 + 5y = 0 Add '-10' to each side of the equation. 10 + -10 + 5y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 5y = 0 + -10 5y = 0 + -10 Combine like terms: 0 + -10 = -10 5y = -10 Divide each side by '5'. y = -2 Simplifying y = -2
| 4w^2+4w+1= | | -4.22-0.807= | | 3x^(1/2)-7x^(1/4)=6 | | -4*10= | | 32x+24y=640 | | 20n+12=16n-16 | | 8x-7=8(x+2) | | 10y-120+3x+45=180 | | 9/5(-10)+32=f | | X+14/13=12/13x | | x+3/12=5/6 | | 9x-(4x-9)=7+4x | | (2x-7)=7 | | 6-8y=5y+19 | | 3t+6t=16-8+28 | | 8(11v)= | | 3^3/2-6=75 | | 40x^2-83x+42=0 | | -25=m-8 | | 3*2-1/5*4+23 | | 2b-5-11b-7= | | 3t+6t=18-8+28 | | 17-1/5(35n+15)=-8n-15 | | ((2*a^-5*b^4*c^3)^-2)/((3*a^3*b^-7*c^3)^2) | | y=3.3x-6.6 | | -3/2+7 | | 45.00(15.00+x)=1935 | | 0.6x-1.7=0.70 | | C=5/9(23-32) | | 3L/5=7 | | 6-6=4z-2z | | A(n)=-2+(n-1)5 |